Recent Progress in Visible-Light-Mediated S-N Bond Cleavage for Intermolecular Two-component Dual Functionalization - Zhao, Yu; Xuan, Jun (Synthesis)
Sulfur- and nitrogen- containing functional groups are fundamental constituents of bioactive molecules and pharmaceuticals, exhibiting diverse pharmacological activities. Recent advances in visible-light-mediated photochemistry have enabled more sustainable and efficient synthetic approaches. This review highlights the emerging strategy of difunctionalization via S-N bond cleavage using bifunctional reagent under visible light irradiation. Key reactions discussed include imino-sulfonylation, imino-sulfamoylation, thiocyanato-imination, and related processes, which enable the simultaneous introduction of sulfur and nitrogen functionalities into alkenes, alkynes, and strained ring systems. Mechanistic pathways involving energy transfer or single-electron transfer facilitate selective radical generation and subsequent cross-coupling, offering broad substrate scope and excellent functional group tolerance. This review provides a critical analysis of current methodologies and outlines future directions for the continued advancement of this rapidly evolving field.